2017
DOI: 10.21037/atm.2017.03.36
|View full text |Cite
|
Sign up to set email alerts
|

The expression of proline-specific enzymes in the human lung

Abstract: The pathophysiology of lung diseases is very complex and proteolytic enzymes may play a role or could be used as biomarkers. In this review, the literature was searched to make an overview of what is known on the expression of the proline-specific peptidases dipeptidyl peptidase (DPP) 4, 8, 9, prolyl oligopeptidase (PREP) and fibroblast activation protein α (FAP) in the healthy and diseased lung. Search terms included asthma, chronic obstructive pulmonary disease (COPD), lung cancer, fibrosis, ischemia reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 136 publications
(151 reference statements)
0
16
0
Order By: Relevance
“…Prolyloligopeptidase is an oligopeptidase with endopeptidase activity. It has been shown to be localised in the cytoplasm but given its ability to inactivate several neuropeptides in vitro by limited proteolysis, its involvement in the in vivo generation of immunoactive peptides and its presence in plasma it most likely also has an extracellular role [ 8 , 16 ]. Membrane-bound POP has also been described [ 17 ].…”
Section: Renin Angiotensin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolyloligopeptidase is an oligopeptidase with endopeptidase activity. It has been shown to be localised in the cytoplasm but given its ability to inactivate several neuropeptides in vitro by limited proteolysis, its involvement in the in vivo generation of immunoactive peptides and its presence in plasma it most likely also has an extracellular role [ 8 , 16 ]. Membrane-bound POP has also been described [ 17 ].…”
Section: Renin Angiotensin Systemmentioning
confidence: 99%
“…It has been widely accepted that a counter-regulatory renin-angiotensin system (RAS) axis including angiotensin (ANG)-converting enzyme 2 (ACE2)/ANG [1-7]/Mas protects the lungs from acute lung injury. However, recent evidence suggests that ACE2 expression is significantly lower in the lungs compared with other organs and tissues [ 7 ] and that generation of the protective ANG [1-7] is predominantly mediated by prolyloligopeptidase (POP), which has repeatedly been demonstrated to be involved in human pathology [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy human lungs, CD26/DPP4 is expressed principally on type I and II alveolar cells, alveolar macrophages, vascular endothelium, and the pleural mesothelium (28). In addition, prior studies have suggested a functional role for CD26/DPP4 in several pulmonary diseases, such as asthma, chronic obstructive pulmonary disease, lung cancer, fibrosis, ischemia-reperfusion injury, and pneumonia (42).…”
Section: Introductionmentioning
confidence: 99%
“…Comorbidities are frequent in COPD and may significantly affect quality of life, escalation of symptoms, and ultimately the survival [15,16]. The pathology of COPD is yet to be fully elucidated however, a dysregulated chronic immune response is thought to be an important driver [38]. DPP-4 modulates the immune response, as previously discussed.…”
Section: Dpp-4 and Copdmentioning
confidence: 90%